2014
DOI: 10.1016/j.cub.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-FOXO3 Signaling Modulates Circadian Rhythms via Regulation of Clock Transcription

Abstract: Circadian rhythms are responsive to external and internal cues, light and metabolism being among the most important. In mammals, the light signal is sensed by the retina and transmitted to the suprachiasmatic nucleus (SCN) master clock [1], where it is integrated into the molecular oscillator via regulation of clock gene transcription. The SCN synchronizes peripheral oscillators, an effect that can be overruled by incoming metabolic signals [2]. As a consequence, peripheral oscillators can be uncoupled from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 34 publications
3
66
0
Order By: Relevance
“…Although the detailed etiologies still need to be unraveled, it is evident that there is a strong relationship between major depression and circadian disruption (Karatsoreos, 2014). Interestingly, clock is a transcriptional target of FoxO3a and the insulin-FoxO3a-Clock signaling pathway plays a key role in the modulation of circadian rhythms, for instance, knock down of FoxO3a dampens circadian amplitude (Chaves et al, 2014;Zheng et al, 2007). These studies revealed an important new role for FoxOs in the regulation of depressive behavior.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Although the detailed etiologies still need to be unraveled, it is evident that there is a strong relationship between major depression and circadian disruption (Karatsoreos, 2014). Interestingly, clock is a transcriptional target of FoxO3a and the insulin-FoxO3a-Clock signaling pathway plays a key role in the modulation of circadian rhythms, for instance, knock down of FoxO3a dampens circadian amplitude (Chaves et al, 2014;Zheng et al, 2007). These studies revealed an important new role for FoxOs in the regulation of depressive behavior.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The pGL3-EV showed a 6.5-fold increase in luminescence (FoxO6-GFP/GFP) (Fig. 6D), suggesting that FoxO6 may regulate transcription in general, as has previously been suggested (22). Importantly, promoter elements containing the confirmed in vivo FoxO6-binding element (pGL3-DBE4) show a significant increase in RLUs (P < 0.01) (FoxO6-GFP/GFP) compared with the control (pGL3-EV) …”
Section: Foxo6 Interacts With Specific Daf-16-binding Elements Withinmentioning
confidence: 63%
“…Meal-induced insulin secretion leads to acute changes of clock gene expression in the liver, including upregulation of Per2 mRNA and downregulation of Rev-erb mRNA [62]. Among the activated intracellular pathways, FoxO3 signalling is able to activate the transcription of the circadian gene Clock [63]. Insulin-mediated signals, however, are probably not the only ones that allow the liver to be synchronized to feeding cues because streptozocin treatment that severely damages -cells does not prevent hepatic synchronization to feeding [7].…”
Section: Insulin As a Postfeeding Timermentioning
confidence: 99%